Lifestyle‐Factors in Adolescence as Predictors of Number of Musculoskeletal Pain Sites in Adulthood: A 17‐Year Follow‐Up Study of a Birth Cohort. Issue 6 (12th February 2015) - Puroila, Antti; Paananen, Markus; Taimela, Simo; Järvelin, Marjo‐Riitta; Karppinen, Jaro
Abstract Objective Musculoskeletal (MS) pain, especially in multiple body sites, may develop into a disabling problem. Still, the long‐term risk factors of MS pain are insufficiently known. We examined whether adverse health behaviors in adolescence are associated with the number of pain sites in adulthood. Setting The study population was a subgroup (n = 5, 737) of the 1966 Northern Finland Birth Cohort, which had answered a postal questionnaire on health behaviors at the age of 14 and a pain questionnaire at approximately 31 years. Results Adverse health behaviors in adolescence, such as occasional smoking (odds ratio (OR) 1.6; 95% confidence interval (CI) 1.0–2.6) and overweight/obesity (1.7; 1.0–2.8) among males, and daily smoking (1.9; 1.0–3.5) and regular use of alcohol (2.2; 1.0–4.8) among females predicted pain in three or more body regions at the age of 31. Physical inactivity (1.6; 1.1–2.5) and moderate physical activity (1.7; 1.1–2.6) were risk factors for two pain sites among females. In addition, the ORs for pain in three or more body regions were high, but the CIs were broad for daily smoking among males and overweight/obesity among females (1.7; 0.8–3.5 and 1.4; 0.8–2.2, respectively). Conclusions As adverse health behaviors in adolescence were moderately associated with multisite MS pains in adulthood, the effectiveness of intervening in adverse health behaviors in adolescence as regards later MS pain should be analyzed.